2004
DOI: 10.1021/ja037783j
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Platinum(II) Vapochromic Salts

Abstract: Luminescent chloride and hexaflurophosphate salts of Pt(Me2bzimpy)Cl+ (Me2bzimpy = 2,6-bis(1-methylbenzimidazol-2-yl)pyridine) are reported. As solids, both compounds are vapochromic, undergoing pronounced and reversible changes of color and emission in the presence of volatile organic compounds. The chloride salt responds to vapors of methanol, chloroform, ethanol, and acetonitrile, undergoing a distinct change in color from yellow to red within seconds. The PF6- salt responded selectively to acetonitrile vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(173 citation statements)
references
References 21 publications
6
164
0
3
Order By: Relevance
“…These vapor-free phases can be collapsed by manual grinding in a mortar to regenerate the initial purple amorphous form, 1P and 2P. The temperature dependences of the luminescence spectra of 1R indicated that the luminescence of 1R was caused by 3 MMLCT (metal-metal-to-ligand charge transfer) emission similar to in 2R; however, the weaker dependence of 1R may be due to enhanced intermolecular π-π stacking interactions caused by the more expanded π-conjugation of H2dcphen than that of H2dcbpy, which would compete with the intermolecular Pt⋅⋅⋅Pt interactions. These results clearly indicate that the Pt(II)-diimine supramolecular system such as 1 and 2 is not only multichromic materials that respond to various external stimuli but also a new type of vaporhistory sensing materials with ON-OFF switching functions based on the shape memory ability derived from the formation and collapse of the porous structure by vapor adsorption and manual grinding, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These vapor-free phases can be collapsed by manual grinding in a mortar to regenerate the initial purple amorphous form, 1P and 2P. The temperature dependences of the luminescence spectra of 1R indicated that the luminescence of 1R was caused by 3 MMLCT (metal-metal-to-ligand charge transfer) emission similar to in 2R; however, the weaker dependence of 1R may be due to enhanced intermolecular π-π stacking interactions caused by the more expanded π-conjugation of H2dcphen than that of H2dcbpy, which would compete with the intermolecular Pt⋅⋅⋅Pt interactions. These results clearly indicate that the Pt(II)-diimine supramolecular system such as 1 and 2 is not only multichromic materials that respond to various external stimuli but also a new type of vaporhistory sensing materials with ON-OFF switching functions based on the shape memory ability derived from the formation and collapse of the porous structure by vapor adsorption and manual grinding, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, vapochromic materials that exhibit color changes upon adsorption/desorption of chemical vapors have attracted considerable attention because of their potential application for sensor devices for detecting vapor from volatile organic compounds (VOCs) which are widely used in our living environments. [2][3][4][5][6][7] Among the known vapochromic materials, square-planar Pt(II) complexes have been extensively studied in recent decades because they are well-known to exhibit color and luminescence changes based on a structural transformation involving modification of the intermolecular metallophilic interactions. [2][3][4][5][6] The vapor-sensing functionalities of most of the vapochromic materials reported so far are usually based on the color difference between the adsorbed and desorbed forms, as shown in Scheme 1(a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 MMLCT emission can thus be observed at longer wavelengths than unimolecular 3 MLCT emission. [40] There is much motivation to develop new materials with novel functions based on these characteristics, in order to expand the range of applications. It is likely that the effect of spatial distribution of the Pt complex inside the mesopores on the photoluminescence emission, as well as on the photocatalytic activity, can be systematically examined, since the interaction between each Pt complex on mesoporous silica materials can be simply controlled by changing the Pt loading.…”
Section: Anchoring Of [Pt(tpy)cl]mentioning
confidence: 99%
“…[4,5] Even though most platinum() complexes are nonluminescent at room temperature, a few of them have been exploited as chemosensors. [6] Recently, Grove et al have discussed the vapochromic properties of [Pt(Me 2 bzimpy)Cl] + , [7] and + as a molecular light switch for proteins, [8] although studies pertaining to this complex have been limited to albumins. Very recently, the same group has demonstrated the molecular light switch effect specifically to human serum albumin (HSA) exhibited by a platinum() com-presence of 6 M urea leads to a decrease in the emission intensity of the complex, which suggests its binding to the hydrophobic pockets of the protein.…”
mentioning
confidence: 99%